SCULPTURE IN THE MODERN ERA: INNOVATIONS IN MATERIALS AND STYLES - Velayutham, Arun; K, Raman (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Modern Era of sculpture has been marked by significant innovations in materials and styles, reflecting broader artistic movements and technological advancements. Traditional materials like marble and bronze have been complemented and sometimes replaced by diverse new media, including plastics, metals, found objects, and digital elements. Artists have experimented with unconventional materials to challenge and expand the boundaries of sculptural form and meaning. Additionally, modern sculpture has embraced various styles, from abstract and minimalist to kinetic and interactive, often breaking away from representational norms. These innovations have allowed for a more dynamic and inclusive exploration of themes, contributing to the evolution of sculpture as a vital and versatile art form in contemporary society.